Chemically strengthened glass

By adopting microcrystalline glass with specific composition and structure, the main crystal phase is zinc-magnesium spinel, and the crystallinity and grain size are within a certain range. Combined with 3D thermal bending treatment, the microcrystalline glass during thermal bending molding is solved. Due to the problems of optical performance deterioration and size changes, excellent optical performance and size control of curved microcrystalline glass are achieved.

CN119409415APending Publication Date: 2025-02-11CHONGQING AUREAVIA HI TECH GLASS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411582475.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the 3D thermal bending process, existing microcrystalline glasses are prone to problems such as deterioration in optical performance and large size changes, making it difficult to prepare curved transparent spinel microcrystalline glasses.

Method used

Microcrystalline glass with specific composition and structure, the main crystal phase is zinc-magnesium spinel (Zn, Mg) Al2O4, with a crystallinity of 20.00-50.00 wt%. It is formed by 3D thermal bending treatment and the average grain size is controlled to be less than 10.00 nm. , satisfies the specific oxide component ratio and relationship formula.

Benefits of technology

It realizes the maintenance of excellent optical performance and dimensional changes that meet the requirements during the 3D thermal bending process, and solves the problems of optical performance deterioration and dimensional changes of microcrystalline glass during the thermal bending molding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409415A_ABST
    Figure CN119409415A_ABST
Patent Text Reader

Abstract

The invention discloses microcrystalline glass, the microcrystalline glass comprises a main crystalline phase (Zn, Mg) Al2O4, the average grain size of the crystalline phase in the microcrystalline glass is less than 10.00 nm, and the crystallinity of the microcrystalline glass is 20.00-50.00 wt%; the microcrystalline glass comprises the following components in percentage by mole of oxide: 38.00-45.00% of SiO2; the content of Al2O3 is 24.00 to 28.00 percent; 13.00% to 20.00% of MgO + ZnO (magnesium oxide + zinc oxide); zrO2: 3.00% to 5.00% of ZrO2; 2.00% to 11.00% of Li2O + Na2O (lithium oxide + sodium oxide); 3.00% to 9.00% of B2O3 (boron trioxide); meanwhile, the content of each oxide in the microcrystalline glass also meets the following relational expression: X = (Na2O + 2.35 * B2O3 + 1.52 * Li2O) / (0.96 * Al2O3), and X is more than or equal to 0.61 and less than or equal to 1.30. The microcrystalline glass with specific composition and microstructure provided by the invention can be molded into qualified curved microcrystalline glass through a 3D hot bending process, that is, the obtained curved microcrystalline glass keeps excellent optical performance, and the size change meets the requirements. According to the transparent spinel glass ceramic disclosed by the invention, the forming and transmittance change controllability in the 3D hot bending process can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of glass technology, and more particularly to a chemically strengthened glass. This invention patent application is a divisional application of the invention patent application with application number 202211666770.0, application date December 23, 2022, and invention name “A kind of microcrystalline glass, curved microcrystalline glass and its application”. Background Art

[0002] With the advent of the smart era, mobile phones have become an indispensable communication tool in daily life. As the number of mobile phone users increases year by year, in order to meet the needs of mobile phone users and improve the user experience, the speed of mobile phone replacement is also increasing. Mobile phone cover glass has evolved from the initial 2D glass to 2.5D glass and now 3D glass, which not only increases the novelty of mobile phone terminal products in terms of appearance, but also improves the user's touch experience.

[0003] There are two main types of front cover glass used in the mobile phone market: one is ordinary glass and the other is microcrystalline glass. The mechanical strength of ordinary glass is far behind that of microcrystalline glass, which is mainly reflected in its poor drop resistance. Among the numerous microcrystalline glass, spinel microcrystalline glass with spinel as the main crystal phase has gradually attracted the attention of industry insiders due to its high Young's modulus and shear modulus.

[0004] When ordinary glass is subjected to 3D heat bending to prepare curved glass, there is generally no change in optical properties. However, when microcrystalline glass is subjected to 3D heat bending, it may be accompanied by crystal growth, that is, the crystal phase content and grain size will change. The crystal phase content and grain size of microcrystalline glass will affect the optical properties of the obtained curved glass, and the growth of crystals is often accompanied by changes in the macroscopic size of the glass. For example, it was found in CN114230183A that when the existing spinel nanocrystalline ceramic glass is processed into a protective cover plate with a complex shape, the ceramic glass is prone to uncontrollable crystallization (secondary crystallization), and the precipitated crystals are not spinel crystal phases and are very large in size. In addition, the original spinel crystal phase in the ceramic glass will regrow at high temperature, and the size uniformity of the crystal phase after regrowth is difficult to control, which destroys the conditions for the glass to maintain high transmittance, resulting in a decrease in the transmittance of the ceramic glass after hot pressing.

[0005] Therefore, how to avoid the problems of optical performance degradation and large dimensional changes faced by microcrystalline glass during the 3D hot bending forming process and prepare curved transparent spinel microcrystalline glass that meets the requirements is a technical problem that the present invention urgently needs to solve. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a chemically strengthened glass. The microcrystalline glass provided by the present invention has spinel as the main crystal phase, and at the same time has a specific composition and structure different from the existing transparent spinel microcrystalline glass. The inventors have found that by performing 3D heat bending on the microcrystalline glass, it is possible to obtain a curved microcrystalline glass with excellent optical properties and dimensional changes that meet the requirements, which solves the problems of optical performance degradation, large dimensional changes, and inability to be heat-bent in the 3D heat bending process of the microcrystalline glass in the prior art.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a glass-ceramic, wherein the glass-ceramic contains a main crystalline phase (Zn, Mg)Al2O4, the average grain size of the crystalline phase in the glass-ceramic is less than 10.00 nm, and the crystallinity of the glass-ceramic is 20.00 to 50.00 wt %;

[0009] Calculated by molar percentage of oxides, the microcrystalline glass includes the following components:

[0010] SiO2: 38.00~45.00%;

[0011] Al2O3: 24.00~28.00%;

[0012] MgO+ZnO: 13.00~20.00%;

[0013] ZrO2: 3.00~5.00%;

[0014] Li2O+Na2O: 2.00~11.00%;

[0015] B2O3: 3.00~9.00%;

[0016] At the same time, the content of each oxide in the microcrystalline glass also satisfies the following relationship:

[0017] X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3), and 0.61≤X≤1.30, in which the oxide represents the molar percentage of the oxide component.

[0018] Preferably, in the glass-ceramics,

[0019] The molar percentage of SiO2 is 38.50% to 44.00%; and / or

[0020] The molar percentage of Al2O3 is 24.00% to 27.50%; and / or

[0021] The molar percentage of ZnO is 8.00% to 12.00%; and / or

[0022] The molar percentage of MgO is 5.00% to 8.00%; and / or

[0023] The molar percentage of ZrO2 is 3.00% to 4.00%; and / or

[0024] The molar percentage of Na2O is 3.00% to 10.00%; and / or

[0025] The molar percentage of B2O3 is 3.50 to 9.00%.

[0026] Preferably, the crystallinity of the glass-ceramics is 30.00 to 50.00 wt %, more preferably 30.00 to 45.00 wt %.

[0027] Preferably, in the glass-ceramics, the average grain size is 1.0 to 9.0 nm, preferably 3.0 to 9.0 nm, and more preferably 5.0 to 8.0 nm.

[0028] Preferably, the relaxation temperature of the glass-ceramics is lower than 850°C, preferably not more than 840°C, more preferably 700-840°C.

[0029] Preferably, in the glass-ceramics, the molar ratio of ZnO to MgO satisfies: 1.60≤ZnO / MgO≤2.00.

[0030] Preferably, in the microcrystalline glass, the molar ratio of SiO2 and Al2O3 satisfies: 1.50≤SiO2 / Al2O3≤1.90.

[0031] Preferably, calculated by molar percentage of oxides, the glass-ceramics further includes 0-3.00% BaO and / or 0-2.00% Y2O3.

[0032] Preferably, the glass-ceramic contains substantially no TiO2.

[0033] Preferably, the microcrystalline glass also contains a secondary crystalline phase, and the secondary crystalline phase includes one or more of tetragonal ZrO2, Zn2SiO4, and Mg2SiO4.

[0034] Preferably, at a thickness of 0.7 mm, for light with a wavelength of 550 nm, the transmittance of the microcrystalline glass is greater than or equal to 85.00%, and preferably the transmittance is greater than or equal to 89.00%.

[0035] Preferably, at a thickness of 0.7 mm, the optical b value of the glass-ceramics is 0.20 to 1.50, preferably 0.50 to 1.20.

[0036] In a second aspect, the present invention also provides a curved microcrystalline glass, which is obtained by forming the above-mentioned microcrystalline glass through 3D heat bending treatment; at a thickness of 0.7 mm, for light of 550 nm wavelength, the transmittance of the curved microcrystalline glass is greater than or equal to 85.00%, and preferably the transmittance is greater than or equal to 88.00%.

[0037] Preferably, the curved glass-ceramics contains a main crystalline phase (Zn, Mg)Al2O4, and the crystallinity of the curved glass-ceramics is 20.00-50.00wt%; and / or, the curved glass-ceramics also contains a secondary crystalline phase, and the secondary crystalline phase includes one or more of tetragonal ZrO2, Zn2SiO4, and Mg2SiO4.

[0038] In a third aspect, the present invention further provides a method for preparing a curved glass-ceramic, comprising the following steps:

[0039] Step I: Select substrate glass, which includes the following components calculated by molar percentage of oxides: SiO2: 38.00-45.00%; Al2O3: 24.00-28.00%; MgO+ZnO: 13.00-20.00%; ZrO2: 3.00-5.00%; Li2O+Na2O: 2.00-11.00%; B2O3: 3.00-9.00%; and satisfies the following formula: X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3), and 0.61≤X≤1.30;

[0040] Step II: heat-treating the substrate glass to obtain the above-mentioned microcrystalline glass;

[0041] Step III: The microcrystalline glass is formed by 3D heat bending to obtain the above-mentioned curved microcrystalline glass.

[0042] Preferably, in the substrate glass, the molar ratio of ZnO to MgO satisfies: 1.60≤ZnO / MgO≤2.00; and / or

[0043] In the substrate glass, the molar ratio of SiO2 and Al2O3 satisfies: 1.50≤SiO2 / Al2O3≤1.90.

[0044] Preferably, the substrate glass further comprises 0-3.00% BaO and / or 0-2.00% Y2O3, calculated by molar percentage of oxides; and / or

[0045] The substrate glass contains substantially no TiO2.

[0046] Preferably, the heat treatment specifically includes:

[0047] First, the substrate glass is heated to the nucleation temperature and kept at this temperature for 0.1 to 72 hours, preferably 0.1 to 24 hours, more preferably 10 to 1440 minutes. The nucleation temperature is T g +ΔT1, 5℃≤ΔT1≤50℃;

[0048] Then the temperature is raised to the crystallization temperature and kept at this temperature for 0.1 to 72 hours, preferably for 0.1 to 24 hours, more preferably for 10 to 1440 minutes. The crystallization temperature is T g +ΔT2, 60℃≤ΔT2≤200℃;

[0049] Among them, T g is the glass transition temperature.

[0050] The curved surface glass-ceramics prepared by the present invention has excellent optical properties. At a thickness of 0.7 mm, for light with a wavelength of 550 nm, the transmittance of the curved surface glass-ceramics is greater than or equal to 85.00%, and preferably the transmittance is greater than or equal to 88.00%. This shows that the technical solution provided by the present invention solves the problem of easy devitrification of glass-ceramics during hot bending.

[0051] In a fourth aspect, the present invention further provides a substrate glass, wherein the substrate glass can be subjected to heat treatment and crystallization to obtain the above-mentioned glass-ceramics;

[0052] Calculated by molar percentage of oxides, the substrate glass includes the following components: SiO2: 38.00~45.00%; Al2O3: 24.00~28.00%; MgO+ZnO: 13.00~20.00%; ZrO2: 3.00~5.00%; Li2O+Na2O: 2.00~11.00%; B2O3: 3.00~9.00%; and the content of each oxide in the substrate glass also satisfies the following relationship: X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3), and 0.61≤X≤1.30.

[0053] Preferably, in the substrate glass, the molar ratio of ZnO to MgO satisfies: 1.60≤ZnO / MgO≤2.00; and / or

[0054] In the substrate glass, the molar ratio of SiO2 and Al2O3 satisfies: 1.50≤SiO2 / Al2O3≤1.90.

[0055] Preferably, the substrate glass further comprises 0-3.00% BaO and / or 0-2.00% Y2O3, calculated by molar percentage of oxides; and / or

[0056] The substrate glass contains substantially no TiO2.

[0057] In a fifth aspect, the present invention further provides a chemically strengthened glass, wherein the chemically strengthened glass is obtained by subjecting the above-mentioned glass-ceramics, the above-mentioned curved glass-ceramics, the curved glass-ceramics obtained by the above-mentioned preparation method, or the above-mentioned substrate glass to chemical strengthening treatment. The chemically strengthened glass comprises a compressive stress layer and a tensile stress layer.

[0058] In a sixth aspect, the present invention further provides a glass device, which is made of the above-mentioned microcrystalline glass or the above-mentioned curved microcrystalline glass or the curved microcrystalline glass prepared by the above-mentioned preparation method or the above-mentioned substrate glass or the above-mentioned chemically strengthened glass.

[0059] In a seventh aspect, the present invention further provides an electronic device, which comprises the above-mentioned microcrystalline glass or the above-mentioned curved microcrystalline glass or the curved microcrystalline glass obtained by the above-mentioned preparation method or the above-mentioned substrate glass or the above-mentioned chemically strengthened glass.

[0060] Compared with the prior art, the present invention has the following beneficial effects:

[0061] The present invention has developed a glass-ceramic solution that is different from the existing transparent spinel glass-ceramic by conducting an in-depth study on the composition and structure of glass-ceramic. The glass-ceramic with a specific composition and microstructure provided by the present invention can be formed into a qualified curved glass-ceramic through a 3D hot bending process, that is, the obtained curved glass-ceramic has excellent optical properties and the dimensional change meets the requirements. The transparent spinel glass-ceramic of the present invention can be formed and the transmittance change can be controlled during the 3D hot bending process. At the same time, the main crystal phase of the glass-ceramic provided by the present invention is zinc-magnesium spinel solid solution (Zn, Mg)Al2O4, and the crystallinity is 20.00~50.00wt%. The (Zn, Mg)Al2O4 crystal phase has a high Young's modulus and shear modulus. Combined with the high crystal content of the glass-ceramic, it is ensured that the glass-ceramic and the curved glass-ceramic made of the glass-ceramic have a high intrinsic strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is the TGA curve of the substrate glass of Example S3.

[0063] Figure 2 This is the XRD spectrum of the glass-ceramics of Example S1.

[0064] Figure 3 This is the transmittance curve of the microcrystalline glass of Example S1.

[0065] Figure 4 Photos of glass-ceramics samples after heat bending of Example S1 and Comparative Example D4 under the same heat bending process;

[0066] Among them, the glass on the left is a photo of the microcrystalline glass of Example S1 after heat bending, and the glass on the right is a photo of the microcrystalline glass of Comparative Example D4 after heat bending.

[0067] Figure 5 This is the XRD spectrum of the glass-ceramic sample before and after hot bending in Example S1.

[0068] Figure 6 Schematic diagram of the relaxation temperature of the glass-ceramics of Example S3.

[0069] Figure 7 This is a photo of the microcrystalline glass of comparative example D2 that was broken during the hot bending process. DETAILED DESCRIPTION

[0070] 1. The relevant special names and relevant measurement methods involved in the present invention are explained as follows.

[0071] Base glass: glass that has not been subjected to nucleation, crystallization or strengthening treatment.

[0072] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that is prepared by targeted and controlled crystallization of the base glass and contains both glass phase and crystal phase (microcrystalline phase, crystalline phase, and crystalline phase).

[0073] Chemically strengthened glass: It is a solid composite material obtained after the glass sample is chemically strengthened. During high-temperature chemical strengthening treatment, the alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the salt bath / molten salt will replace the alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the glass sample, thereby generating an exchange ion volume difference and generating compressive stress on the glass surface. The glass samples here include but are not limited to substrate glass (without crystalline phase), microcrystalline glass, and curved microcrystalline glass.

[0074] Nucleation: Through heat treatment, the nucleating material in the glass grows small crystal nuclei.

[0075] Crystallization: Growing a certain crystal based on the crystal nucleus through heat treatment.

[0076] Crystalline phase: The crystallographic phase is the microscopic structure of the crystal, which is determined by the conformation and arrangement of the polymer chains in the crystal.

[0077] Crystallinity: the percentage of the total mass of crystals / crystalline phases / grains in the total mass of microcrystalline glass. It should be understood that both crystalline phases and grains refer to crystals precipitated in microcrystalline glass.

[0078] Complete crystallization: Under the premise of not generating impurities (such as the glass-ceramics of the present invention preferably does not contain crystalline quartz SS), the crystallinity of the glass-ceramics reaches or approaches the theoretical crystallinity. Theoretical crystallinity refers to the theoretical maximum crystallinity under the glass-ceramics formula system.

[0079] b value: indicates the yellow-blue value of the material. In the present invention, the b value is the b value of transmitted light. A positive b value indicates that the material is blue. It is measured using a Konica Minolta spectrophotometer CM-3600A.

[0080] Transmittance: The ratio of the radiant energy projected and transmitted through an object to the total radiant energy projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other surface. In the embodiments and comparative examples of the present invention, the transmittance of microcrystalline glass at a wavelength of 550nm refers to the average transmittance of multiple glass samples of the same batch measured at a wavelength of 550nm. At least 5 microcrystalline glass samples are taken from each batch for testing.

[0081] Sag temperature: The temperature at which the structure of the sample under test relaxes and begins to collapse during the heating process. For the test method, refer to GB / T 7962.16-2010 Test method for colorless optical glass Part 16: Linear expansion coefficient, transition temperature and sag temperature.

[0082] Hot bending (Yes / No): Hot bending Yes means that the sample can be formed to fit the surface of the mold by its own weight or pressure under certain hot bending process conditions; Hot bending NO means that the sample cannot be formed to fit the surface of the mold by its own weight or pressure under certain hot bending process conditions, including failure to bend in place, such as Figure 4 The glass sample on the right, or the glass breaks after being pressurized, such as Figure 7 of glass samples.

[0083] Glass-ceramic performance index test:

[0084] 1. Optical performance test: According to the standard of GB / T 7962.12-2010 Test method for colorless optical glass Part 12: Spectral transmittance, a professional testing instrument is used to test the b value and transmittance of the microcrystalline glass. The tester used in the present invention is the Konica Minolta Spectrophotometer CM-3600A from Japan.

[0085] 2. XRD test: The crystallized microcrystalline glass is ground into glass fine powder with a grinding machine, and its particle size is less than 75μm, and then it is tested by X-ray diffractometer to obtain XRD diffraction peak curve. Then use professional software to analyze XRD diffraction data to obtain data such as crystallinity and average grain size. The X-ray diffractometer used in the present invention is Shimadzu's XRD-6100, the target material is copper, the diffraction angle range used in the test is 2θ=10~80°, the scanning speed is 0.2~6° / min, the working voltage is 40kV, and the working current is 30mA.

[0086] 3. Test method for crystal content / crystallinity: Import the X-ray diffractometer test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud) for fitting and calculation. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content / crystallinity.

[0087] 4. Average grain size: The microcrystalline glass sample was tested with an X-ray diffractometer. The average grain size was obtained by using the Scherrer formula D = Kλ / (βcosθ), where λ is the X-ray wavelength of 0.154056nm, β is the peak half-width, and K = 0.89.

[0088] 5. Differential Scanning Calorimetry (DSC) Test: The test instrument is Mettler-Toledo TGA / DSC3+ Thermogravimetric and Synchronous Thermal Analyzer. During the test, the sample is ground and passed through a 200-mesh sieve; the test conditions are: room temperature to 1100°C, and a heating rate of 10°C / min.

[0089] 6. 3D hot bending treatment: Set the temperature and time of each station of the 3D hot bending machine (the 3D hot bending machine used in the present invention is DTK-DGP-3D12S) so that each station can reach the preset temperature. Put the microcrystalline glass into the graphite mold, put the graphite mold into the station entrance through the conveyor belt or the feeding port, and take out the mold at the exit after the automatic molding device works automatically.

[0090] 7. Density measurement: The density of the glass-ceramic sample is tested according to the principle of “Archimedes drainage method”. The testing instrument is ALFAMIRAGE electronic density balance SD-200L.

[0091] 8. Sample thickness test: determined by micrometer test.

[0092] 2. A glass-ceramic

[0093] In the prior art, most curved glass uses ordinary glass as raw material, because ordinary glass has no crystal phase, and there is generally no change in optical properties during the hot bending process, so it is easier to obtain curved glass with good optical properties through hot bending. However, the mechanical strength of ordinary glass is far inferior to that of microcrystalline glass, especially the drop resistance, which is far behind that of microcrystalline glass. This also leads to the insufficient mechanical strength of curved glass made of ordinary glass, which cannot meet the use requirements of protective cover plates of high-end electronic products.

[0094] The difficulty in preparing curved glass-ceramics lies in the fact that the crystallization and molding conditions cannot be coordinated and balanced. The crystallization condition includes the type of crystals contained in the glass-ceramics, the crystal content and the grain size, which determine the intrinsic strength and transmittance of the glass-ceramics; while the molding condition includes the shape change and optical property change of the glass-ceramics in the process of changing from flat glass-ceramics to curved glass-ceramics. This process is prone to undesirable phenomena such as inadequate molding, glass fragments, excessive size scaling, and a sharp drop in transmittance. Therefore, when the crystal content is low, hot bending of glass-ceramics is often easier. However, if you want glass-ceramics with higher intrinsic strength, you need to make the glass-ceramics have a higher crystal content and higher strength crystals, such as spinel crystals with high Young's modulus and shear modulus.

[0095] The inventors have found that high-strength crystals often have more regular and denser structural arrangements. After growing in the substrate glass, the volume of the substrate glass will change significantly. For example, for glass-ceramics with spinel as the main crystal phase, the size of the substrate glass will scale by as much as 3.5-14.8% after the crystallization process. In order to ensure that the size change after hot bending meets the requirements, when preparing curved glass-ceramics with spinel as the main crystal phase, it is more suitable to adopt the method of hot bending after complete crystallization, because if a curved spinel glass-ceramic with high crystallinity is to be obtained by hot bending of semi-crystallized (partially crystallized) or uncrystallized glass products, it means that the hot bending process will inevitably be accompanied by the growth of spinel crystals, and the size change caused by the growth of spinel crystals at this stage is uncontrollable, which can easily lead to uneven thickness of the obtained curved glass-ceramics and difficulty in ensuring the uniformity of size. In other words, it is difficult to obtain curved glass-ceramics with spinel as the main crystal phase and high crystallinity that meets the size requirements. The method of hot bending after complete crystallization also faces difficulties. The main problems it faces include: due to the high crystal content and high intrinsic strength of the microcrystalline glass, it is easy to have problems such as incomplete molding and glass breakage; if uncontrollable crystal growth occurs during the hot bending process, the crystal phase composition, crystal phase content and grain size will undergo significant changes, which will easily cause the transmittance of the curved microcrystalline glass to drop sharply and the size of the curved microcrystalline glass to change greatly, making it difficult to ensure dimensional uniformity.

[0096] On this basis, the present invention has developed a glass-ceramic solution that is different from the existing transparent spinel glass-ceramic by conducting in-depth research on the composition and structure of glass-ceramic. The present invention obtains a spinel glass-ceramic with a specific composition and microstructure by precisely regulating the composition and microstructure of glass-ceramic. The glass-ceramic can be formed into a qualified curved glass-ceramic through a 3D hot bending process, that is, the obtained curved glass-ceramic has excellent optical properties and meets the requirements for dimensional changes. The transparent spinel glass-ceramic of the present invention can be formed and the transmittance change can be controlled during the 3D hot bending process. At the same time, the main crystal phase of the glass-ceramic provided by the present invention is zinc-magnesium spinel (Zn, Mg) Al2O4, with a crystallinity of 20.00-50.00wt%. The (Zn, Mg) Al2O4 crystal phase has a high Young's modulus and shear modulus. Combined with the high crystal content of the glass-ceramic, it is ensured that the glass-ceramic and the curved glass-ceramic made of the glass-ceramic have a high intrinsic strength.

[0097] The present invention provides a glass-ceramic, wherein the glass-ceramic contains a main crystalline phase (Zn, Mg)Al2O4, the average grain size of the crystalline phase in the glass-ceramic is less than 10.00 nm, and the crystallinity of the glass-ceramic is 20.00-50.00 wt %;

[0098] Calculated by molar percentage of oxides, the microcrystalline glass includes the following components:

[0099] SiO2: 38.00~45.00%;

[0100] Al2O3: 24.00~28.00%;

[0101] MgO+ZnO: 13.00~20.00%;

[0102] ZrO2: 3.00~5.00%;

[0103] Li2O+Na2O: 2.00~11.00%;

[0104] B2O3: 3.00~9.00%;

[0105] At the same time, the content of each oxide in the microcrystalline glass also satisfies the following relationship:

[0106] X = (Na2O + 2.35 × B2O3 + 1.52 × Li2O) / (0.96 × Al2O3), and 0.61 ≤ X ≤ 1.30, in which the oxide represents the molar percentage of the oxide component. The inventors of the present invention have found that by regulating the types of oxide components in the microcrystalline glass, the content of each component and the ratio between each component, the relaxation temperature of the microcrystalline glass is lower than 850 ° C, the average grain size in the microcrystalline glass is less than 10nm, the main crystal phase is zinc magnesium spinel (Zn, Mg) Al2O4, and the crystallinity is 20.00 ~ 50.00wt%, which can realize the forming and optical controllability of the microcrystalline glass during the hot bending forming process. In the case of complete crystallization to obtain a higher crystal content / crystallinity, it is ensured that the microcrystalline glass can pass a specific 3D hot bending process to obtain a curved microcrystalline glass with excellent optical properties and dimensional changes that meet the requirements.

[0107] SiO2 is a glass network forming oxide and an indispensable component of the glass network structure. Properly increasing the content of SiO2 can increase the stability and mechanical strength of the glass, but excessive SiO2 will increase the viscosity of the base glass, making it more difficult to melt and bend the glass, thereby reducing the formability of the base glass. Therefore, the content of SiO2 in the present invention should not be too high, and its molar percentage is 38.00-45.00%. In some embodiments, the mole percentage of SiO2 can be 38.00% to 39.00%, 38.50% to 44.00%, 39.00% to 42.00%, 40.00% to 43.00%, 42.00% to 45.00%, 41.00% to 45.00%, 41.00% to 44.00%, 38.00%, 38.50%, 39.00%, 40.00%, 41.00%, 42.00%, 43.00%, 44.00%, 45.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0108] Al2O3 is an intermediate oxide in the formation of glass, which can improve the chemical stability of glass. Al2O3 is one of the components of the zinc-magnesium spinel crystal phase formed after the substrate glass is crystallized, which will directly affect the main crystal phase (Zn 1-a Mg a )Al2O 44content. At the same time, since [AlO4] is larger in volume than [SiO4], it can provide more space for ion exchange and promote chemical strengthening. However, excessive Al2O3 will increase the viscosity of the substrate glass, which will reduce the formability of the substrate glass. It will also increase the softening point of the glass, making it difficult to hot-bend the fully crystallized microcrystalline glass. In addition, Al2O3 can form a low eutectic point with ZrO2, Na2O, etc., which promotes the molding of glass. The molar percentage of Al2O3 in the present invention is 24.00-28.00%. In some embodiments, the mole percentage of Al2O3 can be 24.00% to 25.00%, 24.00% to 26.00%, 24.00% to 27.00%, 24.00% to 27.50%, 25.00% to 26.00%, 25.00% to 27.00%, 25.00% to 28.00%, 26.00% to 27.00%, 26.00% to 28.00%, 27.00% to 28.00%, 24.00%, 25.00%, 26.00%, 27.00%, 27.50%, 28.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0109] ZnO provides the zinc necessary for the substrate glass to form a zinc-magnesium spinel crystal phase after crystallization. ZnO can reduce the thermal expansion coefficient of glass and improve the chemical stability, thermal stability and refractive index of glass. MgO contains the magnesium necessary for the substrate glass to crystallize and form a zinc-magnesium spinel crystal phase. MgO can slow down the hardening speed of glass and improve the forming properties of glass; MgO can also reduce the crystallization tendency and crystallization speed, increase the high-temperature viscosity of glass, and improve the chemical stability and mechanical strength of glass. In the present invention, the sum of the molar percentages of ZnO and MgO is: 13.00%≤ZnO+MgO≤20.00%. The greater the total content of ZnO and MgO, the greater the spinel crystal content that can be obtained after the crystallization of the microcrystalline glass, and the higher the crystallinity. However, when the total amount of ZnO and MgO is too large, the grain size will be too large, affecting the optical properties and hot bending effect of the microcrystalline glass. In some embodiments, the sum of the mole percentages of ZnO and MgO can be 13.00% to 15.00%, 14.00% to 16.00%, 15.00% to 17.00%, 13.00% to 18.00%, 14.00% to 19.00%, 15.00% to 20.00%, 16.00% to 20.00%, 16.00% to 19.00%, 13.00%, 14.00%, 15.00%, 16.00%, 17.00%, 18.00%, 19.00%, 20.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0110] In some embodiments of the present invention, in the glass-ceramics, the molar percentage of ZnO is 8.00% to 12.00%. In some embodiments, the molar percentage of ZnO can be 8.00% to 9.00%, 8.00% to 10.00%, 8.00% to 11.00%, 8.00% to 11.50%, 9.00% to 10.00%, 9.00% to 11.00%, 9.00% to 12.00%, 10.00% to 11.00%, 10.00% to 12.00%, 11.00% to 12.00%, 10.50% to 11.50%, 9.50% to 11.50%, 8.00%, 9.00%, 10.00%, 11.00%, 12.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0111] In some embodiments of the present invention, in the glass-ceramics, the molar percentage of MgO is 5.00% to 8.00%. In some embodiments, the molar percentage of MgO can be 5.00% to 6.00%, 5.00% to 7.00%, 5.00% to 7.50%, 6.00% to 7.00%, 6.00% to 8.00%, 7.00% to 8.00%, 6.50% to 8.00%, 5.50% to 7.00%, 5.00%, 6.00%, 6.50%, 7.00%, 8.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.

[0112] ZrO2 has a large accumulation effect on the glass structure due to its high cationic charge and strong field, and acts as a nucleating agent in the substrate glass; at the same time, ZrO2 can also increase the strength and toughness of the microcrystalline glass and improve its corrosion resistance. In addition, ZrO2 is also one of the second crystalline phases of the microcrystalline glass of this system. However, excessive ZrO2 will greatly increase the viscosity of the glass, affect the molding of the substrate glass, and control the spinel transparent microcrystalline glass. The molar percentage of ZrO2 in the present invention is 3.00-5.00%. In some embodiments, the molar percentage of ZrO2 can be 3.00%-4.00%, 3.00%-3.50%, 3.50%-4.00%, 4.50%-5.00%, 3.50%-5.00%, 3.00%, 3.50%, 4.00%, 4.50%, 5.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0113] The microcrystalline glass of the present invention also contains one or more alkali metal oxides, such as Li2O and / or Na2O, which can promote the ion exchange process to chemically strengthen the microcrystalline glass and improve the mechanical strength of the microcrystalline glass. At the same time, the alkali metal oxide, as a network exogenous oxide formed by the glass, will provide free oxygen, destroy the network structure of the glass, and further affect the intrinsic strength of the glass. However, destroying the network structure of the glass is beneficial to reducing the high-temperature viscosity of the glass and promoting the melting and clarification of the glass liquid.

[0114] In the present invention, when the total content of the molar percentage of Li2O+Na2O is too large, it is easy to cause uncontrollable crystallization of the glass, that is, the crystals grow or other impurities appear, resulting in a relatively low glass transmittance. In the present invention, the sum of the molar percentages of Li2O and Na2O is: 2.00%≤Li2O+Na2O≤11.00%. In some embodiments, the sum of the mole percentages of Li2O and Na2O can be 2.00% to 3.00%, 2.00% to 5.00%, 2.00% to 8.00%, 3.00% to 6.00%, 4.00% to 9.00%, 2.00% to 7.00%, 5.00% to 8.00%, 6.00% to 9.00%, 4.00% to 10.00%, 7.00% to 9.00%, 5.00% to 10.00%, 8.00% to 11.00%, 2.00%, 3.00%, 4.00%, 5.00%, 6.00%, 7.00%, 8.00%, 9.00%, 10.00%, 11.00%, and the like, and all ranges and sub-ranges between the above-recited values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0115] In some embodiments of the present invention, the molar percentage of Na2O in the glass-ceramics is 3.00 to 10.00%. + The ion exchange component required for the chemical strengthening process is obtained by + Compared with the Na+ ions with small ionic radius in glass-ceramics +The exchange reaction can generate surface compressive stress on the surface of the microcrystalline glass, further improving the monomer strength and scratch resistance of the microcrystalline glass. In addition, the addition of Na2O can effectively reduce the softening point temperature of the glass, but too much Na2O causes the spinel system substrate glass to crystallize and devitrify during the melting process. In some embodiments, the molar percentage of Na2O can be 3.00% to 7.00%, 3.00% to 5.00%, 4.00% to 8.00%, 3.00% to 6.00%, 4.00% to 9.00%, 4.00% to 7.00%, 5.00% to 8.00%, 6.00% to 9.00%, 3.00%, 4.00%, 5.00%, 6.00%, 7.00%, 8.00%, 9.00%, 10.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0116] In some embodiments of the present invention, the molar percentage of Li2O in the microcrystalline glass is 0 to 5.00%. + Compared with the Li ions with small ionic radius in glass-ceramics + The exchange reaction can form deep stress in the microcrystalline glass, which improves the strength and scratch resistance of the microcrystalline glass monomer while improving the impact resistance of the microcrystalline glass. In some embodiments, the molar percentage of Li2O can be 0-1.00%, 0-2.00%, 0-3.00%, 1.00%-3.00%, 2.00%-4.00%, 2.00%-5.00%, 1.00%-2.00%, 1.00%-4.00%, 0, 1.00%, 2.00%, 3.00%, 4.00%, 5.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0117] B2O3 is generally used as a flux in the glass formation process, which can reduce the high temperature viscosity of the glass, accelerate the clarification of the glass, and reduce the crystallization ability of the glass; it can effectively alleviate the problem of difficulty in melting the base glass due to high content of alumina, and at the same time can effectively reduce the softening point temperature of the glass. However, excessive B2O3 will reduce the chemical stability and mechanical strength of the glass and affect the optical properties of the glass. In the present invention, the molar percentage of B2O3 is 3.00-9.00%. In some embodiments, the mole percentage of B2O3 can be 3.00% to 5.00%, 3.00% to 8.00%, 3.50 to 9.00%, 3.00% to 6.00%, 4.00% to 9.00%, 3.00% to 7.00%, 5.00% to 8.00%, 6.00% to 9.00%, 3.00%, 3.50%, 4.00%, 5.00%, 6.00%, 7.00%, 8.00%, 9.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0118] In the glass-ceramics of the present invention, the content of the main components also satisfies the following relationship: X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3), and 0.61≤X≤1.30. In some embodiments, the value of X can be 0.61-0.70, 0.61-0.80, 0.61-0.90, 0.61-1.20, 0.70-1.30, 0.80-1.10, 0.90-1.20, 0.61, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0119] The glass-ceramics of the present invention is spinel glass-ceramics, and its main crystal phase is (Zn, Mg)Al2O4, that is, zinc-magnesium spinel crystal. Zinc-magnesium spinel crystal has high Young's modulus and shear modulus, which is conducive to improving the mechanical strength performance of glass-ceramics.

[0120] In the glass-ceramics of the present invention, the average grain size of the crystalline phase is less than 10.00 nm, preferably 1.00 nm to 9.00 nm, more preferably 3.00 nm to 9.00 nm, and more preferably 5.00 nm to 8.00 nm. The average grain size in the glass-ceramics directly affects the hot bending formability of the glass-ceramics. In some embodiments, the average grain size can be 1.00nm to 2.00nm, 1.00nm to 5.00nm, 2.00nm to 7.00nm, 3.00nm to 8.00nm, 4.00nm to 9.00nm, 2.00nm to 6.00nm, 3.00nm to 9.00nm, 4.50nm to 6.80nm, 2.60nm to 4.90nm, 3.70nm to 8.60nm, 5.50nm to 7.20nm, 6.20nm to 8.90nm, 1.00nm, 2.00nm, 3.00nm, 4.00nm, 5.00nm, 6.50nm, 7.00nm, 8.00nm, 9.00nm, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0121] In some embodiments of the present invention, the crystallinity of the glass-ceramics is 20.00-50.00 wt %, preferably 30.00-50.00 wt %, and more preferably 30.00-45.00 wt %. High crystallinity / crystal content can give the glass-ceramics higher intrinsic strength. In some embodiments, the crystallinity of the glass-ceramics can be 20.00-35.00wt%, 20.00-40.00wt%, 30.00-35.00wt%, 35.00-40.00wt%, 35.00-45.00wt%, 40.00-50.00wt%, 25.00-35.00wt%, 25.00-45.00wt%, 25.00-50.00wt%, 30.00-40.00wt%, 20.00wt%, 30.00wt%, 40.00wt%, 50.00wt%, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0122] In some embodiments of the present invention, the sag temperature of the glass-ceramics is lower than 850° C., preferably not more than 840° C., and more preferably 700-840° C. The sag temperature will directly determine whether the glass-ceramics can be hot-bent to obtain curved glass-ceramics that meet the requirements. In the present invention, the sag temperature is controlled by regulating the components of the glass-ceramics. In some embodiments, the sag temperature of the glass-ceramics may be 700°C to 720°C, 700°C to 750°C, 720°C to 780°C, 730°C to 760°C, 745°C to 795°C, 715°C to 795°C, 765°C to 815°C, 755°C to 825°C, 730°C to 815°C, 765°C to 835°C, 770°C to 830°C, 700°C, 725°C, 730°C, 755°C, 760°C, 770°C, 780°C, 800°C, 820°C, 840°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0123] In some embodiments of the present invention, in the glass-ceramics, the molar ratio of ZnO and MgO satisfies: 1.60≤ZnO / MgO≤2.00. ZnO / MgO largely determines whether the glass-ceramics can be transparent after crystallization. The present invention can ensure that transparent glass-ceramics with excellent optical properties are obtained after crystallization by regulating ZnO / MgO within a specific range. In some embodiments, the value of ZnO / MgO can be 1.70-1.80, 1.60-1.70, 1.60-1.80, 1.60-1.90, 1.70-1.90, 1.70-2.00, 1.80-2.00, 1.90-2.00, 1.60, 1.70, 1.80, 1.90, 2.00, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.

[0124] In some embodiments of the present invention, in the microcrystalline glass, the molar ratio of SiO2 and Al2O3 satisfies: 1.50≤SiO2 / Al2O3≤1.90.

[0125] When SiO2 / Al2O3 is too high, stratification is easy to occur during glass molding, and when SiO2 / Al2O3 is too low, the melting difficulty of glass increases. Therefore, the present invention controls the molar ratio between SiO2 / Al2O3 and controls it between 1.50≤SiO2 / Al2O3≤1.90. In some embodiments, the value of SiO2 / Al2O3 can be 1.50-1.60, 1.50-1.70, 1.50-1.80, 1.60-1.70, 1.60-1.80, 1.60-1.90, 1.70-1.90, 1.80-1.90, 1.50, 1.60, 1.70, 1.80, 1.90, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0126] In some embodiments of the present invention, the microcrystalline glass further includes 0-3.00% BaO and / or 0-2.00% Y2O3 calculated by molar percentage of oxides.

[0127] BaO can increase the refractive index of the glass phase in microcrystalline glass, and can reduce the difficulty of melting, and can be used as a flux. In the present invention, the molar percentage of BaO is 0 to 3.00%. In some embodiments, the molar percentage of BaO can be 0 to 1.00%, 0 to 1.50%, 1.00% to 1.50%, 1.00% to 2.00%, 1.50% to 2.00%, 1.50% to 3.00%, 2.50% to 3.00%, 1.00% to 3.00%, 0, 1.00%, 1.50%, 2.00%, 2.50%, 3.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0128] Y2O3 can reduce the viscosity of glass and promote the melting and clarification of glass liquid. In the present invention, the molar percentage of Y2O3 is 0-2.00%. In some embodiments, the molar percentage of Y2O3 can be 0-1.00%, 0-1.50%, 1.00%-1.50%, 1.00%-2.00%, 1.50%-2.00%, 0, 1.00%, 1.50%, 2.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0129] In some embodiments of the present invention, the glass-ceramic contains substantially no TiO2.

[0130] In some embodiments of the present invention, the microcrystalline glass further comprises a secondary crystalline phase, and the secondary crystalline phase comprises one or more of tetragonal ZrO2, ZnSiO4, and Mg2SiO4.

[0131] In some embodiments of the present invention, at a thickness of 0.7 mm, for light of 550 nm wavelength, the transmittance of the microcrystalline glass is greater than or equal to 85.00%, preferably greater than or equal to 89.00%, 85.00% to 88.00%, 86.00% to 88.00%, 85.00% to 89.00%, 88.00% to 89.00%, 90.00% to 91.00%, 88.00% to 92.00%, 89.00% to 83.00%, 89.00% to 84.00%, 81.00% to 86.00% to 87.00%, 81.00% to 88.00%, 81.00% to 89 ... %, 91.00%, 89.00% to 92.00%, 90.00% to 93.00%, 90.00% to 96.00%, 92.00% to 96.00%, 88.00%, 89.00%, 90.00%, 91.00%, 92.00%, 93.00%, 94.00%, 95.00%, 96.00%, 97.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0132] In some embodiments of the present invention, at a thickness of 0.7 mm, the optical b value of the microcrystalline glass is 0.20 to 1.50, preferably 0.50 to 1.20, 0.30 to 0.50, 0.40 to 0.80, 0.30 to 0.70, 0.45 to 0.89, 0.23 to 0.67, 0.70 to 1.03, 0.50 to 1.20, 0.80 to 1.40, 0.60 to 1.50, 0.20, 0.50, 0.60, 0.70, 0.90, 1.20, 1.50, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0133] In the present invention, those skilled in the art can select the thickness of the microcrystalline glass according to the requirements. Exemplarily, the thickness of the microcrystalline glass is 0.2-5.0 mm.

[0134] 3. A curved glass-ceramic

[0135] The present invention also provides a curved microcrystalline glass, which is obtained by forming the above-mentioned microcrystalline glass through 3D hot bending treatment; at a thickness of 0.7 mm, for light of 550 nm wavelength, the transmittance of the curved microcrystalline glass is greater than or equal to 85.00%, and preferably the transmittance is greater than or equal to 88.00%.

[0136] In some embodiments of the present invention, preferably, the curved glass-ceramic contains a main crystalline phase (Zn, Mg)Al2O4, and the crystallinity of the curved glass-ceramic is 20.00-50.00wt%; and / or, the curved glass-ceramic further contains a secondary crystalline phase, and the secondary crystalline phase includes one or more of tetragonal ZrO2, Zn2SiO4, and Mg2SiO4. Preferably, the curved glass-ceramic includes a main crystalline phase of zinc-magnesium spinel (Zn, Mg)Al2O4 and a secondary crystalline phase of tetragonal ZrO2.

[0137] 4. A method for preparing curved glass-ceramics

[0138] In the prior art, there are mainly the following methods for preparing curved glass-ceramics:

[0139] (1) Hot bending first, then crystallization: This process is suitable for microcrystalline glass with little difference in density between crystal and glass, no obvious change in crystallization volume, or very low crystallinity;

[0140] (2) Partial crystallization first, and complete full crystallization while hot bending: This process is suitable for glass-ceramics with high crystallinity and no obvious change in crystallization volume, such as glass-ceramics containing petalite and lithium disilicate;

[0141] (3) First fully crystallize, then heat bend; this process is suitable for low-crystallization glass-ceramics or glass-ceramics with large crystallization volume changes.

[0142] When the crystal content in glass-ceramics is low, hot bending of glass-ceramics is relatively easy, and any of the above processes can be used for hot bending. However, this also means that the obtained curved glass-ceramics do not have sufficient intrinsic strength, which also leads to the fact that the curved glass-ceramics do not take advantage of the original high intrinsic strength of glass-ceramics. To improve the intrinsic strength of curved glass-ceramics, higher crystal content and higher strength crystals are required in the glass-ceramics. Crystals with high strength often have more regular and denser structural arrangements. When they grow in the substrate glass, the volume of the substrate glass will change significantly. For example, for glass-ceramics with spinel as the main crystal phase, the size of the substrate glass can be scaled by as much as 3.5 to 14.8% after the substrate glass is completely crystallized. If a semi-crystallized (partially crystallized) or non-crystallized glass product is selected for hot bending to obtain a curved spinel glass-ceramic with high crystallinity, it means that the hot bending process will inevitably be accompanied by the growth of spinel crystals, and the dimensional changes brought about by the growth of spinel crystals at this stage are uncontrollable, which can easily lead to uneven thickness of the obtained curved glass-ceramic and difficulty in ensuring dimensional uniformity, that is, it is difficult to obtain a curved glass-ceramic that meets the dimensional requirements and has spinel as the main crystalline phase and a high degree of crystallinity. Therefore, such glass-ceramics as the present invention, which have high-strength spinel crystals as the main crystalline phase, are basically unable to obtain curved glass-ceramics with relatively good crystallization and forming conditions through the two hot bending processes (1) and (2). When this type of glass-ceramic is prepared into a curved glass-ceramic, it is more suitable to use the (3) process for hot bending treatment. However, the process (3) is also difficult. The main problems faced by the method of hot bending after complete crystallization in the process (3) include: high crystal content and high intrinsic strength of microcrystalline glass, which are prone to problems such as incomplete molding and glass breakage; if uncontrollable crystal growth occurs during the hot bending process, the crystal phase composition, crystal phase content and grain size will undergo significant changes, which will easily cause the transmittance of the curved microcrystalline glass to drop sharply and the size of the curved microcrystalline glass to change greatly, making it difficult to ensure dimensional uniformity.

[0143] The present invention has developed a glass-ceramic solution that is different from the existing transparent spinel glass-ceramic by conducting an in-depth study on the composition and structure of glass-ceramics. The spinel glass-ceramic with a specific composition and microstructure provided by the present invention can be formed into a qualified curved glass-ceramic through a 3D hot bending process, that is, the obtained curved glass-ceramic has excellent optical properties and meets the requirements for dimensional changes. The curved glass-ceramic prepared by the present invention has stronger zinc-magnesium spinel crystals as the main crystal phase, and has a high crystal content / crystallinity, which ensures that the curved glass-ceramic has a high intrinsic strength.

[0144] The method for preparing the curved surface glass-ceramics provided by the present invention comprises the following steps:

[0145] Step I: Select substrate glass, which includes the following components calculated by molar percentage of oxides: SiO2: 38.00-45.00%; Al2O3: 24.00-28.00%; MgO+ZnO: 13.00-20.00%; ZrO2: 3.00-5.00%; Li2O+Na2O: 2.00-11.00%; B2O3: 3.00-9.00%; and satisfies the following formula: X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3), and 0.61≤X≤1.30;

[0146] Step II: After the substrate glass is subjected to complete crystallization heat treatment, the above-mentioned microcrystalline glass is obtained; the microcrystalline glass contains a main crystalline phase (Zn, Mg)Al2O4, the average grain size of the crystalline phase in the microcrystalline glass is less than 10.00nm, and the crystallinity of the microcrystalline glass is 20.00-50.00wt%;

[0147] Step III: The microcrystalline glass is formed by 3D hot bending to obtain the above-mentioned curved microcrystalline glass. At a thickness of 0.7 mm, for light of 550 nm wavelength, the transmittance of the curved microcrystalline glass is greater than or equal to 85.00%, and preferably the transmittance is greater than or equal to 88.00%. The curved microcrystalline glass contains a main crystalline phase (Zn, Mg)Al2O4, and the crystallinity of the curved microcrystalline glass is 20.00-50.00wt%; and / or, the curved microcrystalline glass also contains a secondary crystalline phase, and the secondary crystalline phase includes one or more of tetragonal ZrO2, Zn2SiO4, and Mg2SiO4. Preferably, the curved microcrystalline glass includes a main crystalline phase of zinc-magnesium spinel (Zn, Mg)Al2O4 and a secondary crystalline phase of tetragonal ZrO2.

[0148] In some embodiments of the present invention, in the substrate glass, the molar ratio of ZnO to MgO satisfies: 1.60≤ZnO / MgO≤2.00; and / or

[0149] In the substrate glass, the molar ratio of SiO2 and Al2O3 satisfies: 1.50≤SiO2 / Al2O3≤1.90.

[0150] In some embodiments of the present invention, the substrate glass further comprises 0-3.00% BaO and / or 0-2.00% Y2O3, calculated as the molar percentage of oxides; and / or the substrate glass contains substantially no TiO2.

[0151] In some embodiments of the present invention, a precision annealing furnace is used to sequentially perform nucleation treatment, crystallization treatment or non-separate nucleation and crystallization treatment on the substrate glass to obtain a transparent microcrystalline glass. It should be understood that when the substrate glass is heat-treated, a one-step heat treatment can be performed or a two-step or multi-step heat treatment can be performed. If a one-step heat treatment is performed, it means that the nucleation treatment / nucleation treatment is not performed separately, and the nucleation and target crystal growth are directly performed in a one-step heating process, that is, the crystallization treatment is directly performed. If a two-step heat treatment is performed, it means that a nucleation treatment, i.e., a nucleation treatment, is first performed, and then a target crystal growth treatment, i.e., a crystallization treatment, is performed.

[0152] In some embodiments of the present invention, the complete crystallization heat treatment process comprises: heating the substrate glass to T g +ΔT2, 60℃≤ΔT2≤200℃, where T g The temperature is the glass transition temperature and is kept warm for 0.1 to 72 hours, preferably 0.1 to 24 hours, and more preferably 10 to 1440 minutes.

[0153] In some embodiments of the present invention, the complete crystallization heat treatment comprises heat treating the substrate glass at least at a nucleation temperature for at least 10 minutes; and heat treating at least at a crystallization temperature for at least 10 minutes.

[0154] In some embodiments of the present invention, the heat treatment specifically comprises:

[0155] First, the substrate glass is heated to the nucleation temperature and kept at this temperature for 0.1 to 72 hours, preferably for 0.1 to 24 hours, and more preferably for 10 to 1440 minutes; the nucleation temperature is T g +ΔT1, 5°C≤ΔT1≤50°C. Then raise the temperature to the crystallization temperature and keep it warm for 0.1 to 72 hours, preferably 0.1 to 24 hours, more preferably 10 to 1440 minutes; the crystallization temperature is T g +ΔT2, 60℃≤ΔT2≤200℃. Where, T g is the glass transition temperature.

[0156] In some embodiments of the present invention, when heat treatment is performed, the heating rate is controlled to be 5 to 30°C / min, preferably 5 to 15°C / min. In some implementations, when heat treatment is performed on the substrate glass, the temperature is raised to the nucleation temperature at a heating rate of 10°C / min, and after the nucleation treatment for a certain period of time, the temperature is raised to the crystallization temperature at a heating rate of 10°C / min to perform crystallization treatment.

[0157] The nucleation temperature and the crystallization temperature are adjusted according to the glass transition temperature. Exemplarily, in the present invention, the nucleation temperature is controlled between 650°C and 850°C, for example, 650°C to 700°C, 700°C to 750°C, 750°C to 800°C, 800°C to 850°C, 700°C to 720°C, 680°C to 760°C, 650°C, 680°C, 700°C, 710°C, 730°C, 740°C, 750°C to 780°C, 790°C, 800°C, 810°C, 830°C, 850°C, etc., and all ranges and sub-ranges between the above values. The crystallization temperature is controlled at 700°C to 1000°C, for example, 700°C to 800°C, 800°C to 900°C, 900°C to 1000°C, 750°C to 850°C, 850°C to 950°C, 850°C to 1000°C, 700°C, 800°C, 900°C, 1000°C, etc., and all ranges and sub-ranges between the above values.

[0158] In some embodiments of the present invention, glass-ceramic bricks can be prepared by the above-mentioned heat treatment method, and glass-ceramic sheets that can be used for 3D hot bending can be obtained by cold working the glass-ceramic bricks. The cold working treatment here includes shaping and slicing. Exemplarily, after slicing, CNC processing, grinding, and polishing can be performed in sequence, or after slicing, at least one of CNC processing, grinding, and polishing can be selected to modify the glass sheet to obtain a glass-ceramic sample with a length, width, and thickness of 73mm×50mm×0.7mm. The obtained glass-ceramic sample is then subjected to 3D hot bending to prepare curved glass-ceramic.

[0159] In some embodiments of the present invention, the 3D hot bending process is performed in a 3D hot bending machine; the 3D hot bending process includes the steps of preheating, hot bending forming, and cooling performed sequentially.

[0160] In some embodiments, preheating is divided into four stages. Specifically, the glass-ceramics is placed in a graphite mold, enters an automatic molding device through a conveyor belt or a feeding port, and is preheated through four temperature intervals. Preheating can stabilize the glass heating rate, ensure the thermal stability of the glass, and prevent the glass from cracking due to sudden heating. In this stage, the shape of the glass does not change significantly. In each preheating stage, the glass-ceramics is placed at the corresponding working temperature and kept warm for the corresponding working time. Among them:

[0161] The working temperature of the first stage L1 is 500-650°C and the working time is 1-1800s;

[0162] The working temperature of the second stage L2 is 600-750°C and the working time is 1-1800s;

[0163] The working temperature of the third stage L3 is 700-800°C and the working time is 1-1800s;

[0164] The working temperature of the fourth stage L4 is 750-830°C, and the working time is 1-1800s.

[0165] In some embodiments, the hot bending forming is divided into three stages. Specifically, after preheating, the glass-ceramics in the graphite mold is subjected to three stages of continuous hot pressing at different temperatures for hot bending forming to obtain curved glass-ceramics. The forming stage requires precise control of the temperature of each stage, because this stage determines the forming of the glass and whether crystals are precipitated, wherein:

[0166] The working temperature of the first stage M1 is 750-850°C and the working time is 1-1800s;

[0167] The working temperature of the second stage M2 is 750-850°C and the working time is 1-1800s;

[0168] The working temperature of the third stage M3 is 750-850°C and the working time is 1-1800s.

[0169] In some embodiments, cooling is divided into two stages. Specifically, after hot bending, the obtained curved glass-ceramics is cooled by continuous cooling at different temperatures in two stages. The cooling can control the rapid cooling of the glass and prevent the glass from cracking due to sudden cooling.

[0170] The working temperature of the first stage N1 is 600-700°C and the working time is 1-1800s;

[0171] The working temperature of N2 in the second stage is 400-500°C and the working time is 1-1800s.

[0172] 5. A substrate glass

[0173] The present invention also provides a substrate glass, which can be used to obtain the above-mentioned microcrystalline glass after heat treatment and crystallization of the substrate glass;

[0174] Calculated by molar percentage of oxides, the substrate glass includes the following components: SiO2: 38.00~45.00%; Al2O3: 24.00~28.00%; MgO+ZnO: 13.00~20.00%; ZrO2: 3.00~5.00%; Li2O+Na2O: 2.00~11.00%; B2O3: 3.00~9.00%; and the content of each oxide in the substrate glass also satisfies the following relationship: X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3), and 0.61≤X≤1.30.

[0175] In some embodiments of the present invention, in the substrate glass, the molar ratio of ZnO to MgO satisfies: 1.60≤ZnO / MgO≤2.00; and / or

[0176] In the substrate glass, the molar ratio of SiO2 and Al2O3 satisfies: 1.50≤SiO2 / Al2O3≤1.90.

[0177] In some embodiments of the present invention, the substrate glass further comprises 0-3.00% BaO and / or 0-2.00% Y2O3, calculated as the molar percentage of the oxides; and / or

[0178] The substrate glass contains substantially no TiO2.

[0179] In the present invention, the composition of the substrate glass is the same as that of the microcrystalline glass in terms of the molar percentage of oxides. The molding methods of the substrate glass include, but are not limited to, float, overflow, rolling and casting. Exemplarily, the raw material components are evenly mixed according to the formula, and after melting and molding, they are cooled and annealed to obtain the substrate glass. For example, the substrate glass raw materials can be melted at a melting temperature of 1480°C to 1650°C, the molten glass liquid can be molded, and after molding, it can be cooled and annealed to obtain the substrate glass. The preferred annealing temperature is 500°C to 650°C, and the annealing is preferably kept warm for 12 to 48 hours.

[0180] In the present invention, when preparing the substrate glass, a clarifier may be added to the substrate glass, the clarifier including but not limited to SnO2, Sb2O3, and NaCl; based on the mass of the substrate glass, the amount of the clarifier added is 0.01wt% to 2.00wt%, preferably 0.01wt% to 1.50wt%.

[0181] 6. A chemically strengthened glass

[0182] The present invention also provides a chemically strengthened glass, which is obtained by chemically strengthening the above-mentioned glass-ceramics, the above-mentioned curved glass-ceramics, the curved glass-ceramics obtained by the above-mentioned preparation method, or the above-mentioned substrate glass. The chemically strengthened glass comprises a compressive stress layer and a tensile stress layer.

[0183] It should be understood that after the chemical strengthening ion exchange process, the composition of the surface of the glass-ceramic / substrate glass / curved glass-ceramic (i.e., the compressive stress layer) may be different from the composition of the newly formed glass-ceramic / substrate glass / curved glass-ceramic (i.e., before the ion exchange process). This is because during the ion exchange, one type of alkali metal ion (e.g., Li + Or Na+ ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced by, such as Na in glass + K in strengthening salt bath + Exchange, K + Replaced by, and / or, Li in glass + and Na in the strengthening salt bath + Exchange, by Na + However, in an embodiment, the composition of the glass-ceramic / substrate glass / curved glass-ceramic at the center of the depth of the glass article or near the center of the depth (i.e., the tensile stress layer) will still have the composition of the just-formed glass-ceramic / substrate glass / curved glass-ceramic.

[0184] Since the chemical strengthening process mainly involves the exchange of alkali metal ions, and the main crystalline phase of the microcrystalline glass of the present invention is (Zn, Mg)Al2O4, and the secondary crystalline phase includes one or more of tetragonal ZrO2, zinc silicate Zn2SiO4, and magnesium silicate Mg2SiO4, does not contain alkali metals, and does not participate in ion exchange. Therefore, the main crystalline phase of the chemically strengthened glass obtained by strengthening the microcrystalline glass is still (Zn, Mg)Al2O4, and the secondary crystalline phase includes one or more of tetragonal ZrO2, Zn2SiO4, and Mg2SiO4.

[0185] It should be understood that the transmittance of the glass-ceramics / substrate glass / curved glass-ceramics of the present invention will not substantially change after chemical strengthening treatment, and therefore, the chemically strengthened glass is transparent in the visible light range.

[0186] In the present invention, when chemical strengthening treatment is performed, the microcrystalline glass / substrate glass / curved microcrystalline glass is placed in a high-temperature salt bath containing potassium salt and / or sodium salt, and the strengthening treatment is performed for a certain period of time to obtain the chemically strengthened glass, wherein the salt bath temperature can be 380-600°C, and the salt bath can also contain 0-1wt% of lithium salt. The potassium salt includes one or more of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; the sodium salt includes one or more of sodium nitrate, sodium sulfate, and sodium carbonate, preferably sodium nitrate; the lithium salt includes one or more of lithium nitrate, lithium sulfate, and lithium carbonate, preferably lithium nitrate.

[0187] 7. A glass device

[0188] The present invention also provides a glass device, which is made of the above-mentioned microcrystalline glass or the above-mentioned curved microcrystalline glass or the curved microcrystalline glass prepared by the above-mentioned preparation method or the above-mentioned substrate glass or the above-mentioned chemically strengthened glass.

[0189] The glass device of the present invention may be regular or irregular, and those skilled in the art may manufacture it according to the requirements.

[0190] 8. An electronic device

[0191] The present invention also provides an electronic device, which comprises the above-mentioned microcrystalline glass or the above-mentioned curved microcrystalline glass or the curved microcrystalline glass obtained by the above-mentioned preparation method or the above-mentioned substrate glass or the above-mentioned chemically strengthened glass.

[0192] The electronic device described in the present invention includes but is not limited to at least one of a mobile phone, a display (such as a car display, an aircraft display, etc.), a tablet computer, an electronic watch, a smart wearable (such as a smart bracelet, a smart watch, smart glasses), and a television.

[0193] In the electronic device of the present invention, a layer may or may not be provided on the surface of the cover.

[0194] Exemplarily, the electronic device provided by the present invention comprises: a housing comprising a front surface, a back surface and a side surface; an electronic component at least partially located within the housing, the electronic component comprising at least a controller, a memory and a display, the display being located at the front surface of the housing or adjacent to the front surface of the housing; and: a covering substrate arranged above the display, wherein at least a portion of at least one of the housing or the covering substrate comprises the curved microcrystalline glass as described in any of the preceding claims.

[0195] The glass-ceramics and strengthened glass-ceramics of the present invention have excellent properties and can be included / applied in other products, as well as any products requiring a certain degree of transparency or other combinations.

[0196] IX. EXAMPLES AND COMPARATIVE EXAMPLES

[0197] Take Example S1 as an example:

[0198] (1) Preparation of substrate glass:

[0199] According to the formula, 1000g of raw materials are mixed and mixed for 30 minutes. After mixing, 5g of NaCl, a clarifier, is added. The resulting mixture is placed in a platinum crucible and melted at 1650°C for 5 hours, then poured into a mold for molding and cooling. After cooling to 900°C, it is placed in a 620°C annealing furnace for 12 hours, and then cooled to room temperature with the furnace to obtain the substrate glass. The substrate glass preparation of other embodiments and comparative examples is the same as that of Example S1.

[0200] (2) Preparation of glass-ceramics:

[0201] After the substrate glass is subjected to nucleation treatment and crystallization treatment in sequence using a precision annealing furnace, a transparent microcrystalline glass is obtained. Specifically, the temperature is raised to the nucleation temperature of 690°C at a heating rate of 10°C / min and kept at this temperature for 240 minutes; then, the temperature is raised to the crystallization temperature of 760°C at a heating rate of 10°C / min and kept at this temperature for 240 minutes to obtain a microcrystalline glass brick.

[0202] (3) Cold processing: The above-mentioned microcrystalline glass bricks are subjected to cold processing, and the cold processing includes shaping and slicing to obtain microcrystalline glass sheets of required sizes. The specifications of the processed microcrystalline glass sheets in the embodiment of the present invention are: microcrystalline glass sheets with a length, width and thickness of 73 mm × 50 mm × 0.7 mm.

[0203] After the slicing process, CNC processing, grinding processing, and polishing processing can be performed in sequence, or after the slicing process, at least one of CNC processing, grinding processing, and polishing processing can be selected to perform glass sheet modification processing.

[0204] (4) Preparation of curved glass-ceramics:

[0205] The above-mentioned microcrystalline glass sheet is placed in a 3D hot bending machine and subjected to 3D hot bending to prepare a curved microcrystalline glass. The 3D hot bending process includes the steps of preheating, hot bending and cooling.

[0206] Among them, the working temperatures of each stage in the preheating process are: L1: 450°C, L2: 600°C, L3: 650°C, L4: 760°C; the working temperatures of each stage in the hot bending process are: M1: 850°C, M2: 800°C, M3: 600°C; the working temperatures of each stage in the slow cooling process are: N1: 450°C, N2: 300°C; the working time of each stage is 90s. The preparation process of the curved microcrystalline glass in other embodiments and comparative examples is the same as that in embodiment S1.

[0207] As needed, the substrate glass, microcrystalline glass, and curved microcrystalline glass obtained in the above steps can be chemically strengthened to prepare chemically strengthened glass with better performance. When performing chemical strengthening treatment, the microcrystalline glass / substrate glass / curved microcrystalline glass is placed in a high-temperature salt bath containing potassium salt and / or sodium salt, and strengthened for a certain period of time to obtain chemically strengthened glass, wherein the salt bath temperature can be 380-600°C, and the salt bath can also contain 0-1wt% of lithium salt. The potassium salt includes one or more of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; the sodium salt includes one or more of sodium nitrate, sodium sulfate, and sodium carbonate, preferably sodium nitrate; the lithium salt includes one or more of lithium nitrate, lithium sulfate, and lithium carbonate, preferably lithium nitrate.

[0208] Table 1 Formula table of Examples S1 to S8 and Comparative Examples D1 to D4 (in mol% of oxide)

[0209]

[0210]

[0211] Table 2 Heat treatment process of the embodiment and the comparative example and characteristic parameters of the microcrystalline glass before and after heat bending

[0212]

[0213]

[0214] Note: The "zinc-magnesium spinel" in Table 2 is the (Zn, Mg)Al2O4 zinc-magnesium spinel solid solution.

[0215] As can be seen from Table 1, the present invention strictly controls the content of each oxide in Examples S1 to S8. As can be seen from Table 2, the sag temperatures of the microcrystalline glasses of Examples S1 to S8 are all lower than 850°C. Combined with controlling the average grain size of the microcrystalline glass to be less than 10nm, the crystallinity of the microcrystalline glasses of Examples S1 to S8 is maintained at more than 34.00%, the transmittance of 550nm wavelength light is maintained at more than 89.00%, and the optical b value is between 0.50-1.20, with excellent optical properties and intrinsic strength. Moreover, before and after hot bending, the transmittance, b value, crystal phase composition and crystallinity of the microcrystalline glasses of Examples S1 to S8 basically did not change significantly, and still maintained excellent optical properties.

[0216] This shows that the present invention makes the relaxation temperature of the glass-ceramics lower than 850°C by precisely controlling the components and microstructure of the glass-ceramics, and controls the average size of the grains in the glass-ceramics to be less than 10nm. On the one hand, under the condition that the main crystalline phase is a zinc-magnesium spinel solid solution, a higher degree of crystallinity is obtained, which ensures that the glass-ceramics have a higher intrinsic strength, while also ensuring that the obtained glass-ceramics have excellent optical properties, and are transparent glass-ceramics with higher transmittance. On the other hand, the forming and optical controllability of the glass-ceramics during the hot bending forming process are achieved. In the case of complete crystallization to obtain a higher degree of crystallinity, the glass-ceramics can still be processed through a specific 3D hot bending process to obtain curved glass-ceramics with excellent optical properties and dimensional changes that meet the requirements.

[0217] However, since the oxide composition of comparative example D1 does not meet the formulation requirements of the present invention, the sag temperature of the obtained microcrystalline glass is higher than 850°C. Under the same hot bending process as S1, its microcrystalline glass cannot be hot-bent into a curved microcrystalline glass. Although comparative example D2 meets the formulation requirements of the present invention, the average grain size of the microcrystalline glass does not meet the requirements of the scheme of the present invention. The average grain size of its microcrystalline glass is too large. Finally, under the same hot bending process as S1, the microcrystalline glass of D2 was broken when hot-bent. Figure 7 As shown. Since the oxide composition of comparative example D3 does not meet the formula requirements of the present invention, although it can be hot-bent, after hot-bending, a mixed phase quartz solid solution appears in the microcrystalline glass, resulting in a sharp drop in the transmittance of the microcrystalline glass. Since the oxide composition of comparative example D4 does not meet the formula requirements of the present invention, its microcrystalline glass cannot be hot-bent into a curved microcrystalline glass under the same hot-bending process as S1. The microcrystalline glass of D4 after hot-bending is as shown. Figure 4 shown.

[0218] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A chemically strengthened glass, characterized in that: The chemically strengthened glass is obtained by subjecting microcrystalline glass to chemical strengthening treatment, and the chemically strengthened glass comprises a compressive stress layer and a tensile stress layer; the composition of the tensile stress layer of the chemically strengthened glass, calculated by molar percentage of oxides, comprises the following components: SiO2: 38.00~45.00%; Al2O3: 24.00~28.00%; MgO+ZnO: 13.00-20.00%; wherein the molar percentage of ZnO is 8.00%-12.00%, and the molar percentage of MgO is 5.00%-8.00%; ZrO2: 3.00~5.00%; Li2O+Na2O: 3.00-11.00%; wherein the molar percentage of Na2O is 3.00%-10.00% and the molar percentage of Li2O is 0-3.00%; B2O3: 3.00~9.00%; At the same time, in the composition of the tensile stress layer of the chemically strengthened glass, the content of each oxide also satisfies the following relationship: X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3), 0.61≤X≤1.30; 1.50≤SiO2 / Al2O3≤1.90; In the relationships, oxide represents the mole percent of the oxide component.

2. The chemically strengthened glass according to claim 1, wherein: The microcrystalline glass is a flat microcrystalline glass or a curved microcrystalline glass. Preferably, the average grain size of the crystalline phase in the microcrystalline glass is less than 10.00 nm, preferably the average grain size is 1.0-9.0 nm, 3.0-9.0 nm or 5.0-8.0 nm, more preferably, the crystallinity of the microcrystalline glass is 20.00-50.00 wt%, preferably the crystallinity is 30.00-50.00 wt% or 30.00-45.00 wt%.

3. The chemically strengthened glass according to claim 1 or 2, characterized in that: The main crystalline phase of the chemically strengthened glass is (Zn, Mg)Al2O4. Preferably, the secondary crystalline phase of the chemically strengthened glass includes one or more of tetragonal ZrO2, Zn2SiO4, and Mg2SiO4.

4. The chemically strengthened glass according to any one of claims 1 to 3, characterized in that: The chemically strengthened glass is transparent in the visible light range. Preferably, the thickness of the chemically strengthened glass is 0.2-5.0 mm. More preferably, at a thickness of 0.7 mm, for light with a wavelength of 550 nm, the transmittance of the chemically strengthened glass is greater than or equal to 85.00%, and preferably the transmittance is greater than or equal to 89.00%.

5. The chemically strengthened glass according to any one of claims 1 to 4, characterized in that: The chemically strengthened glass has a tensile stress layer composed of: The molar percentage of SiO2 is 38.50% to 44.00%, preferably 39.00% to 44.00%; and / or, The molar percentage of Al2O3 is 24.00% to 27.50%, preferably 24.00% to 27.00%; and / or, The molar percentage of ZnO is 9.00% to 11.00%; and / or, The molar percentage of MgO is 5.00% to 7.00%; and / or, The molar percentage of ZrO2 is 3.00% to 4.00%, preferably 3.00% to 3.69%; and / or, The molar percentage of Na2O is 4.00% to 10.00%, preferably 5.00% to 10.00%, more preferably 6.00% to 10.00%; and / or, The molar percentage of B2O3 is 3.50 to 9.00%.

6. The chemically strengthened glass according to any one of claims 1 to 5, characterized in that: The chemically strengthened glass has a tensile stress layer composed of: The molar ratio of ZnO to MgO satisfies: 1.60≤ZnO / MgO≤2.00, preferably 1.60≤ZnO / MgO≤1.90; and / or the molar ratio of SiO2 to Al2O3 satisfies: 1.50≤SiO2 / Al2O3≤1.80; And / or, the value of X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3) is 0.61 to 1.

25.

7. The chemically strengthened glass according to any one of claims 1 to 6, characterized in that: The composition of the tensile stress layer of the chemically strengthened glass further includes 0 to 3.00% BaO and / or 0 to 2.00% Y2O3, calculated by molar percentage of oxides; and / or, The tensile stress layer of the chemically strengthened glass substantially does not contain TiO2.

8. The chemically strengthened glass according to any one of claims 1 to 7, characterized in that: The chemically strengthened glass can be obtained by placing the glass-ceramics in a high-temperature salt bath containing potassium salt and / or sodium salt for chemical strengthening treatment, wherein the salt bath temperature is preferably 380-600° C., and more preferably the salt bath further contains 0-1 wt % of lithium salt; Preferably, the potassium salt includes one or more of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; preferably, the sodium salt includes one or more of sodium nitrate, sodium sulfate, and sodium carbonate, preferably sodium nitrate; Preferably, the lithium salt includes one or more of lithium nitrate, lithium sulfate, and lithium carbonate, preferably lithium nitrate.

9. A chemically strengthened glass, characterized in that: The chemically strengthened glass is obtained by chemically strengthening curved microcrystalline glass, and the chemically strengthened glass comprises a compressive stress layer and a tensile stress layer; the composition of the tensile stress layer of the chemically strengthened glass, calculated by molar percentage of oxides, comprises the following components: SiO2: 38.00~45.00%; Al2O3: 24.00~28.00%; MgO+ZnO: 13.00~20.00%; ZrO2: 3.00~5.00%; Li2O+Na2O: 2.00~11.00%; B2O3: 3.00~9.00%; At the same time, in the composition of the tensile stress layer of the chemically strengthened glass, the content of each oxide also satisfies the following relationship: X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3), 0.61≤X≤1.30, in which the oxide represents the molar percentage of the oxide component.

10. The chemically strengthened glass according to claim 9, wherein: The curved glass-ceramics is obtained by forming glass-ceramics through 3D heat bending. Preferably, at a thickness of 0.7 mm, for light of 550 nm wavelength, the transmittance of the curved glass-ceramics is greater than or equal to 85.00%, preferably the transmittance is greater than or equal to 88.00%, and more preferably, the crystallinity of the curved glass-ceramics is 20.00-50.00wt%.

11. The chemically strengthened glass according to claim 9 or 10, characterized in that: The main crystalline phase of the chemically strengthened glass is (Zn, Mg)Al2O4. Preferably, the secondary crystalline phase of the chemically strengthened glass includes one or more of tetragonal ZrO2, Zn2SiO4, and Mg2SiO4.

12. The chemically strengthened glass according to any one of claims 9 to 11, characterized in that: The chemically strengthened glass is transparent in the visible light range. Preferably, the thickness of the chemically strengthened glass is 0.2-5.0 mm. More preferably, at a thickness of 0.7 mm, for light with a wavelength of 550 nm, the transmittance of the chemically strengthened glass is greater than or equal to 85.00%, and preferably the transmittance is greater than or equal to 88.00%.

13. The chemically strengthened glass according to any one of claims 9 to 12, characterized in that: The chemically strengthened glass has a tensile stress layer composed of: The molar percentage of SiO2 is 38.50% to 44.00%, preferably 39.00% to 44.00%; and / or The molar percentage of Al2O3 is 24.00% to 27.50%, preferably 24.00% to 27.00%; and / or The molar percentage of ZnO is 8.00% to 12.00%, preferably 9.00% to 11.00%; and / or The molar percentage of MgO is 5.00% to 8.00%, preferably 5.00% to 7.00%; and / or The molar percentage of ZrO2 is 3.00% to 4.00%, preferably 3.00% to 3.69%; and / or The molar percentage of Na2O is 3.00% to 10.00%, preferably 5.00% to 10.00%, more preferably 6.00% to 10.00%; and / or The molar percentage of B2O3 is 3.50 to 9.00%.

14. The chemically strengthened glass according to any one of claims 9 to 13, characterized in that: The chemically strengthened glass has a tensile stress layer composed of: The molar ratio of ZnO to MgO satisfies: 1.60≤ZnO / MgO≤2.00, preferably, 1.60≤ZnO / MgO≤1.90; and / or, The molar ratio of SiO2 to Al2O3 satisfies: 1.50≤SiO2 / Al2O3≤1.90, preferably, 1.50≤SiO2 / Al2O3≤1.80; and / or, The value of X=(Na2O+2.35×B2O3+1.52×Li2O) / (0.96×Al2O3) is 0.61~1.

25.

15. The chemically strengthened glass according to any one of claims 9 to 14, characterized in that: The composition of the tensile stress layer of the chemically strengthened glass further comprises 0 to 3.00% BaO and / or 0 to 2.00% Y2O3, calculated by molar percentage of oxides; and / or, The tensile stress layer of the chemically strengthened glass substantially does not contain TiO2.

16. The chemically strengthened glass according to any one of claims 9 to 15, characterized in that: The chemically strengthened glass can be obtained by placing the curved glass-ceramics into a high-temperature salt bath containing potassium salt and / or sodium salt for chemical strengthening treatment, wherein the salt bath temperature is preferably 380-600° C., and more preferably the salt bath further contains 0-1 wt % of lithium salt; Preferably, the potassium salt includes one or more of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; preferably, the sodium salt includes one or more of sodium nitrate, sodium sulfate, and sodium carbonate, preferably sodium nitrate; Preferably, the lithium salt includes one or more of lithium nitrate, lithium sulfate, and lithium carbonate, preferably lithium nitrate.

17. A glass device, characterized in that: The glass device is made of the chemically strengthened glass according to any one of claims 1 to 8 or the chemically strengthened glass according to any one of claims 9 to 16.

18. An electronic device, characterized in that: The electronic device comprises the chemically strengthened glass according to any one of claims 1 to 8 or the chemically strengthened glass according to any one of claims 9 to 16. Preferably, the electronic device comprises at least one of a mobile phone, a display, a tablet computer, an electronic watch, a smart wearable, and a television.

Citation Information

Patent Citations

  • Ceramic glass, curved ceramic glass and preparation method thereof

    CN114230183A